Peningkatan Science Process Skills dan Sikap Ilmiah pada Pembelajaran Fisika Melalui Implementasi CTL - Rahmawati, Ana Silfiani; Ika, Yasinta Embu (Universitas Hamzanwadi, 2019)
This study aims to find out the improvement of the science of process skill and scientific attitude of students through the implementtation of Contextual Teaching and Learning (CTL). This research used in this study is Classroom action research using the Kemmis & Mc Taggart model which consist of two cycles each cycle through the stages of planning, implementation, observation and reflection. The result of this study shows that the implementation of learning in cycle II was more increased compared to the learning process in cycle I. this is indicated by the value of N-Gain Sciences process skills in the first cycle of 0.432 while in the second cycle increased to 0.70; and N-Gain for scientific attitudes in cycle I was 0.252 while in cycle II it increased to 0.392